Multiple sclerosis: Serum anti-CNS autoantibodies - Prineas, John W; Parratt, John D.E (Multiple sclerosis, 2018)
Background: It is uncertain whether there are autoantibodies detectable by indirect immunofluorescence in the serum of patients with multiple sclerosis (MS). Objective: To determine whether there are anti-central nervous system (CNS) autoantibodies detectable by indirect immunofluorescence in the serum of MS patients. Methods: Sera and in some cases cerebrospinal fluid from 106 patients with multiple sclerosis, 156 patients with other neurological diseases, and 70 healthy control subjects were examined by indirect immunofluorescence using cryostat sections of rat cerebrum fixed by perfusion with paraformaldehyde. Results: Autoantibodies were detected that recognized more than 30 neuronal, glial, and mesodermal structures in 28 of 106 MS cases. Most were also detected in patients with other related and unrelated neurological diseases and several were also found in healthy controls. Novel anti-CNS autoantibodies recognizing particular sets of interneurons were detected in both normal controls and in subjects with CNS diseases. Interpretation: Serum anti-CNS autoantibodies of diverse specificities are common in MS patients. The same anti-CNS autoantibodies are not uncommon in patients with other neurological diseases. The findings provide no support for the proposition that myelin breakdown in MS is caused by exposure of intact myelin sheaths or oligodendrocytes to a pathogenic serum anti-myelin or anti-oligodendrocyte autoantibody.